2014
DOI: 10.1007/s00264-014-2562-0
|View full text |Cite
|
Sign up to set email alerts
|

Growth factors in orthopaedic surgery: demineralized bone matrix versus recombinant bone morphogenetic proteins

Abstract: During recent decades the utilisation of growth factors, especially BMPs, has received an increasing interest in orthopaedic surgery. For clinical implantation the two main options are demineralised bone matrix (DBM) and recombinant bone morphogenetic proteins (rhBMP). Many clinical studies agree on an equivalent osteoinductive effect between DBM, BMPs and autologous bone graft; however, the different origins and processing of DBM and rhBMP may introduce some fluctuations. Their respective characteristics are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 101 publications
(102 reference statements)
0
22
0
1
Order By: Relevance
“…These findings are also consistent with the increased skeletogenesis‐related gene expression reported in bone fracture healing (Bais et al, ) and guided bone regeneration (Al‐Kattan et al, ; Donos, Retzepi, et al, ) in a rat model as well as during osseointegration in humans (Donos, Hamlet, et al, ; Ivanovski, Hamlet, Salvi, et al, ) at the 14‐day time point. Additionally, signaling pathways related to the upregulation of osteogenesis‐related genes included the Tgf‐β/Bmp, Wnt, and Notch pathways, which have been demonstrated to be involved in bone regeneration as well as in mesenchymal stem cell and osteoblast differentiation (Argintar, Edwards, & Delahay, ; Canalis, Parker, Feng, & Zanotti, ; Chen & Alman, ; Hinsenkamp & Collard, ; Olivares‐Navarrete, Hyzy, Wieland, Boyan, & Schwartz, ; Zanotti & Canalis, ). Furthermore, research has shown that activation of Wnt and Tgf‐β/Bmp signaling pathways can promote the osteogenic differentiation of mesenchymal stem cells and osteoblasts on the SLActive dental implant surface (Olivares‐Navarrete et al, ; Vlacic‐Zischke, Hamlet, Friis, Tonetti, & Ivanovski, ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are also consistent with the increased skeletogenesis‐related gene expression reported in bone fracture healing (Bais et al, ) and guided bone regeneration (Al‐Kattan et al, ; Donos, Retzepi, et al, ) in a rat model as well as during osseointegration in humans (Donos, Hamlet, et al, ; Ivanovski, Hamlet, Salvi, et al, ) at the 14‐day time point. Additionally, signaling pathways related to the upregulation of osteogenesis‐related genes included the Tgf‐β/Bmp, Wnt, and Notch pathways, which have been demonstrated to be involved in bone regeneration as well as in mesenchymal stem cell and osteoblast differentiation (Argintar, Edwards, & Delahay, ; Canalis, Parker, Feng, & Zanotti, ; Chen & Alman, ; Hinsenkamp & Collard, ; Olivares‐Navarrete, Hyzy, Wieland, Boyan, & Schwartz, ; Zanotti & Canalis, ). Furthermore, research has shown that activation of Wnt and Tgf‐β/Bmp signaling pathways can promote the osteogenic differentiation of mesenchymal stem cells and osteoblasts on the SLActive dental implant surface (Olivares‐Navarrete et al, ; Vlacic‐Zischke, Hamlet, Friis, Tonetti, & Ivanovski, ).…”
Section: Discussionmentioning
confidence: 99%
“…BMP-2, BMP-4, BMP-6, BMP-7 and BMP-9 induce osteogenic differentiation of MSCs in vitro and in vivo [4, 5]. By binding type I and II receptors to form complexes on the cell surface, BMPs exert their biological function through the activation of Smad signaling pathways, which regulate osteogenic-related gene expression [6, 7]. Meanwhile, BMPs are functionally modulated by a class of intracellular and extracellular BMP-binding proteins, termed BMP antagonists [2, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Hinsenkamp and Collard [56] recently reported the importance of concentration of rhBMP that may introduce some interactions with the effectiveness. The difference in concentration between DBM (demineralised bone matrix) and BMPs can vary to a magnitude order of 10 6 , and this may explain the variability in efficiency and the adverse effects.…”
Section: Discussionmentioning
confidence: 99%